Magnetic and Mössbauer spectroscopy studies of hollow microcapsules made of silica-coated CoFe2O4 nanoparticles. (8th December 2015) - Lyubutin, I S; Gervits, N E; Starchikov, S S; Lin, Chun-Rong; Tseng, Yaw-Teng; Shih, Kun-Yauh; Wang, Cheng-Chien; Chen, I-Han; Ogarkova, Yu L; Korotkov, N Yu
Abstract: The hollow microcapsules made of silica-coated CoFe2 O4 nanoparticles were synthesized using chemical co-precipitation, followed by the sol–gel method. Poly(MMA-co-MAA) microspheres were used as a core template which can be completely removed after annealing at 450 °C. The microcapsules are monodisperse with the outer diameter of about 450 nm and the thickness of the shell is about 50 nm. The nanoparticles of Co-ferrite are single crystalline. The size of the nanoparticles and magnetic properties of CoFe2 O4 /SiO2 hollow spheres can be tuned with high accuracy at the annealing stage. The Mössbauer data indicate that CoFe2 O4 ferrite is an inverse spinel, in which Fe 3+ and Co 2+ ions are distributed in both octahedral and tetrahedral sites with the inversion degree close to the bulk ferrite value. At low temperature the CoFe2 O4 /SiO2 nanoparticles are in antiferromagnetic (AFM) state due to the canted or triangular magnetic structure. Under heating in the applied field, AFM structure transforms to the ferrimagnetic (FM) structure, that increases the magnetization. The Mössbauer data revealed that the small size CoFe2 O4 /SiO2 particles do not show superparamagnetic behavior, but they transit to the paramagnetic state by the jump-like first order magnetic transition (JMT). This effect is a specific property of the magnetic nanoparticles isolated by inert material. The suggested method of synthesis can be modified with various bio-ligands on the silane surface, and such materials can find many applications in diagnostics and bio-separation.